2013
DOI: 10.1186/1742-2094-10-125
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation induces neuro-lymphatic protein expression in multiple sclerosis brain neurovasculature

Abstract: BackgroundMultiple sclerosis (MS) is associated with ectopic lymphoid follicle formation. Podoplanin+ (lymphatic marker) T helper17 (Th17) cells and B cell aggregates have been implicated in the formation of tertiary lymphoid organs (TLOs) in MS and experimental autoimmune encephalitis (EAE). Since podoplanin expressed by Th17 cells in MS brains is also expressed by lymphatic endothelium, we investigated whether the pathophysiology of MS involves inductions of lymphatic proteins in the inflamed neurovasculatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 72 publications
3
28
0
Order By: Relevance
“…VEGF-D is also one of the most potent lymphangiogenic factors [18] and plays an important role in neuronal synaptic activity, dendritic length, and dendrite arborization [19]. We observed the alteration of VEGF-D expression levels in EAE/MS settings [16]. These observations indicate that CNS neuroinflammatory diseases alter neuro-lymphatic protein expressions that are involved in the clearance of fluids from the CNS diseases [20,21].…”
Section: Lymphatic Vessel-mediated Immune Cell Efflux Shown By Cns Ausupporting
confidence: 49%
See 1 more Smart Citation
“…VEGF-D is also one of the most potent lymphangiogenic factors [18] and plays an important role in neuronal synaptic activity, dendritic length, and dendrite arborization [19]. We observed the alteration of VEGF-D expression levels in EAE/MS settings [16]. These observations indicate that CNS neuroinflammatory diseases alter neuro-lymphatic protein expressions that are involved in the clearance of fluids from the CNS diseases [20,21].…”
Section: Lymphatic Vessel-mediated Immune Cell Efflux Shown By Cns Ausupporting
confidence: 49%
“…In addition, regarding the immune cell efflux from the CNS, we have identified altered expressions of lymphatic molecules such as LYVE-1, VEGF-D, etc. [16]. Here, LYVE-1 is suggested to be involved in lymph angiogenesis [17].…”
Section: Lymphatic Vessel-mediated Immune Cell Efflux Shown By Cns Aumentioning
confidence: 99%
“…Through control of lymphoid chemokine production in epithelial and fibroblastic stromal cells, IL‐22 also drives lymphoid neogenesis in mice following salivary gland cannulation with adenovirus 23. Podoplanin and IL‐17 have also been linked with ectopic lymphoneogenesis in human diseases 21, 24, 25…”
Section: Cellular Initiators Of Ectopic Lymphoneogenesismentioning
confidence: 99%
“…However, as previous studies by Chaitanya et al showed for the first time that lymphatic molecules, present in serum (and apparently originating within the CNS), could be used to distinguish healthy individuals from those with remitting-relapsing MS versus secondary progressive MS, it is anticipated that CNS lymphatics/glymphatics might represent appropriate targets in forms of neuroinflammation and neurodegeneration. 162 Further studies to determine when the activation, regulation and remodeling of such lymphatic networks are adaptive and can be exploited as innovative therapeutic, diagnostic and prognostic targets are clearly warranted, and are not limited to settings of IBD, myocardial and CNS disturbances with applications in nearly all organ systems. 112,157,163 …”
Section: Lymphatics As Targets For Therapeutic Management Of Inflammamentioning
confidence: 99%